Peningkatan Jaringan Pemasaran Produk Lokal Ikan Salai Patin melalui Program Pengembangan Produk Unggulan Daerah - Dewi Fortuna Ayu; Andarini Diharmi; Evy Rossi; Syahrul Syahrul (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The activities of regional superior product development program (RSPDP) in 3rd year at small and medium-sized micro enterprises (SMME) Putra Niaga aim to increase the capacity and marketing network of salai patin fish as local products from Lubuk Agung Village of Kampar Regency, Riau Province.Â  The steps taken are to design and diversify packaging, expand the marketing network through online media, and construct packaging houses/ showrooms of salai fish products. The results of the activities showed that the activities carried out had an impact on the wider reach of marketing, the variety of types of products produced, increased production capacity, the number of workers, and increased sales turnover.Â  In general, during the Covid 19 pandemic, Putra Niaga SMME was able to sustain the welfare of the community in Lubuk Agung Village by providing jobs and absorbing raw materials for fresh catfish from Kampar Regency.